TRÍADE OFTÁLMICA DOS CÃES BRAQUICEFÁLICOS E TRATAMENTO POR CANTOPLASTIA MEDIAL DE WYMAN: RELATO DE CASO - Oliveira, CELY RAQUEL MATIAS DE (2018)
Brachycephalic dogs are quite predisposed to ophthalmic conditions due to their anatomical characteristics. The ophthalmic triad, composed of caruncular trichiasis, medial entropion and trichiasis of the nasal folds, is a frequent disease. This study aimed to report cases of dogs with the ophthalmic triad and to alert the veterinary clinician about the common existence of this disease, the importance of the diagnosis and its form of treatment. Four Shih tzus and two Pugs were treated at the Veterinary Hospital of the Federal University of Paraíba, from October 2014 to April 2017, presenting clinical signs resulting from the ophthalmic triad. At the ophthalmic examination the animals were diagnosed with the triad or with at least two of the conditions that compose it. Their age ranged from nine months to three years. The surgical treatment instituted was the Wyman's medial canthoplasty technique, which consists in the exeresis of a triangular fragment of the conjunctiva’s medial corner to remove the entire lacrimal caruncle, preserving the superior and inferior lacrimal canaliculi with the aid of the plastic portion of an intravenous cateter. The resection of the protruding nasal folds was associated with the canthoplasty in those dogs that had them. After the stitches were removed, 10 days after surgery, all the dogs presented good cosmetic results and resolution of clinical signs. Thus, it is concluded that the Wyman’s medial canthoplasty is a feasible surgical technique for the correction of the brachycephalic ophthalmic triad, with the advantage of diminishing the eyelid fissure and avoiding proptosis in these dogs.